Strategi Pembelajaran Pendidikan Agama Islam Berbasis Pendekatan Saintifik di Sekolah Dasar dan Madrasah Ibtidaiyah - Fatmawati, Fatmawati (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to explore the application of scientific approach-based Islamic Education learning strategies at SD Al-Ittihadiyah Mamiyai Bromo, as well as the challenges faced in its implementation. The scientific approach, which emphasizes the development of critical and analytical thinking skills, was applied to make students more active and engaged in Islamic learning. The results of the study indicate that the observation, experimentation, and discussion methods used in IEP based on a scientific approach are effective in increasing student engagement in learning and deepening their understanding of Islamic teachings. However, the main challenges faced are limited technological facilities, changes in the mindset of teachers and students, and limited time allocation for more interactive learning. Nevertheless, the application of the scientific approach has a positive impact on improving students' understanding of Islam and helping them apply religious teachings in their daily lives. This study contributes to the development of more relevant and applicable methods of Islamic education in Madrasah Ibtidaiyah.